Modificando o perfil da sala de aula: uma triangulação entre métodos ativos de ensino, TDIC e física moderna e contemporânea - Saccol, Lucas Dellinghausen (2024)
The Physics Education in the Brazilian basic education is out of step with the needs and interests of students and society in general. If the particularities of Physics itself, such as the high level of abstraction and difficulty in understanding, were no longer enough for the subjects academic failure and students lack of interest, the national guidelines reduced even more the time of the class instructions, creating a frightening scenario. Furthermore, the perpetuation of traditional teaching methods, such as expositive, centered on the professor, and the lack of diversity of resources, do not favor the teaching and learning process, nor the interest in Physics. This research is oriented towards the Education of Modern Physics in High School, in contrast to a predominantly Classical Physics program, which is equally outdated. This current Physics, developed since the beginning of the 20th century, is lacking in High School, in parallel with a Physics that is confirmed as a cultural element with the latest great discoveries in Particle Physics, for example. From this general framework, in the search for new methodological paths that place the student at the center of the teaching and learning process, Active Methodologies were selected, supported by Digital Information and Communication Technologies (DCIT), to promote an Active Technological Learning, as a knowledge construction strategy, together with the meaningful learning theory. Therefore, with this triangulation of Active Methodologies, DCIT and Modern Physics, were investigated: how does the integrated use of Active Methodologies and DCIT, in an Active Technological Learning process, contribute to the meaningful learning of Modern Physics in High School students? To answer the proposed research question, a systematic literature review was carried out with the theme, verifying a gap in the Education of Modern Physics with Active Methodologies in the Brazilian High School. Still at systematic literature review, the PER-based Design was identified and adopted, which underlies five principles of all activities of the Modern Physics didactic proposition, oriented to a conceptual and phenomenological approach with the Just-in-Time Teaching and the Peer Instruction, permeated by PhET computer simulations. In applying the proposition in the public High School of the state of Rio Grande do Sul, the data was collected with didactic activities, opinion questionnaires and teachers diaries, which brings positive results with the analysis of integrated use of Active Methodologies and DCIT for teaching Modern Physics concepts, in which seven students showed meaningful learning with the assimilation of the concepts of blackbody radiation, photons, photoelectric effect and wave-particle duality; with Peer Instruction, arousing interest in students, along with Modern Physics topics and confirming itself as an Active Methodology proper for teaching concepts. In addition, the computer and computer simulations were essential to the conceptual and phenomenological approach with their graphic representations, also arousing interest in students, in which the simulations were used in an expositive way by the teacher, and in an exploratory way with manipulation of variables by students of phenomena. In short, the choice of PER-based Design corroborated in several aspects the construction of the didactic proposition, as a potentially meaningful material, and the change in the profile of the classroom with an Active Technological Learning. Finally, a greater number of students did not achieve signs of significant learning due to factors such as low class attendance and lack of commitment — a requirement for protagonism in their learning — and should be considered by teachers and researchers who challenge themselves to use Active Methodologies in the High School.